STUDENT’S PERCEPTION TOWARD ONLINE GAME-MOBILE LEGEND IN LEARNING ENGLISH AT SMAN 1 KECAMATAN MUNGKA - Rahmalia, Indah; Nifriza, Ifna; Cahyani, Regita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Online games can be an effective tool for learning English. Online game can provide an interactive and engaging way for students to practice their English skills in a fun and immersive environment. One of the most popular games is Mobile Legends. This game has a chat feature that allows players to communicate with each other.This can be a great opportunity for students to practice their written communication skills and learn new vocabulary and slang words commonly used by native speakers. The aim of this research is to determine students' perceptions of the online game Mobile Legends in learning English at SMA N 1 Mungka District.Researchers use qualitative methods. The population of this study were class XI students at SMA Negeri 1 Mungka District who played the Mobile Legends game. Researchers used a questionnaire as a data collection tool consisting of 30 statements. Researchers used a modified questionnaire in the form of a Likert scale and also used percentiles to analyze the questionnaire data.The results of this research show that class XI students at SMA Negeri 1 Mungka District have a good perception of the use of the online game Mobile Legends in learning English. This can be seen from the average score of students' perception of the online game Mobile Legends in English language learning is 61%. So it can be said that their perception is quite good in learning English through Mobile Legends.Keywords: online game,mobile legend, English Learning, students perception